2022
DOI: 10.1002/adfm.202210754
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation Regulation and Anchoring of Halide Ions in All‐Inorganic Perovskite Solar Cells Assisted by CuInSe2 Quantum Dots

Abstract: Ionic feature of halide perovskites may lead to the formation of defect states in the polycrystalline films, which can deteriorate the device performance. To solve this issue, a low‐temperature seed‐assisted growth method can contribute to defect‐passivated CsPbI1.2Br1.8 perovskite films by introducing CuInSe2 quantum dots (QDs). As a result, the migration channels inside perovskite grains can be obviously suppressed, but few positive effects on the ions migration in grain boundaries. Conversely, this appearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
2
3
0
Order By: Relevance
“…The absorption spectra in Figure 2b indicate that the control film and the [BMP] + [BF 4 ] −modified CsPbI 1.2 Br 1.8 films process a similar sharp-cutting absorption edge at ~605 nm corresponding to a bandgap of ~2.05 eV, which is consistent with the values reported in the literature [39,41]. However, this increase in mass concentration leads to a slight decrease in the absorption intensity in the 500-580 nm absorption region, mainly due to the addition of [BMP] + [BF 4 ] − in the perovskite films.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The absorption spectra in Figure 2b indicate that the control film and the [BMP] + [BF 4 ] −modified CsPbI 1.2 Br 1.8 films process a similar sharp-cutting absorption edge at ~605 nm corresponding to a bandgap of ~2.05 eV, which is consistent with the values reported in the literature [39,41]. However, this increase in mass concentration leads to a slight decrease in the absorption intensity in the 500-580 nm absorption region, mainly due to the addition of [BMP] + [BF 4 ] − in the perovskite films.…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, the peak intensity of the perovskite film decreases as the mass concentration of the [BMP] + [BF 4 ] − increases to 3 mg mL −1 . This suggests that higher mass concentrations may weaken the crystallinity of the modified films with increased scattering from grain boundaries or intragranular defects, which is not beneficial for the photovoltaic performance of the final devices[40].The absorption spectra in Figure2bindicate that the control film and the [BMP] + [BF 4 ] −modified CsPbI 1.2 Br 1.8 films process a similar sharp-cutting absorption edge at ~605 nm corresponding to a bandgap of ~2.05 eV, which is consistent with the values reported in the literature[39,41]. However, this increase in mass concentration leads to a slight decrease in the absorption intensity in the 500-580 nm absorption region, mainly due to the addition of [BMP] + [BF 4 ] − in the perovskite films.…”
supporting
confidence: 88%
“…As depicted in Figure a, the SCLC curve can be segmented into three distinct regions: the ohmic region, defect filling region, and child region. Experimental data reveals that the carrier mobility is lower in the FAPbI 3 -based device (0.74 × 10 –3 cm 2 V –1 s –1 ) compared to that of the Au/FAPbI 3 -based device (1.46 × 10 –3 cm 2 V –1 s –1 ), indicating that the constructed HETC could accelerate electron migration . Furthermore, transient photovoltage (TPV) measurements demonstrate that the Au/FAPbI 3 -based device exhibits a longer decay time (from 8.49 ms to 16.40 ms ) compared to the FAPbI 3 -based device.…”
Section: Resultsmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain PIHS in hybrid halide perovskites. ,, Among them, defect induced ion segregation has attracted the attention of numerous researchers. Barker et al suggested that the gradient of carrier generation rate generated inside the film drives the separation of halide phases, thus resulting in an iodide-rich low band gap region close to the illuminated surface of the film .…”
Section: Introductionmentioning
confidence: 99%